Aspek Budaya Jawa pada Novel De Winst Karya Afifah Afra: Tinjauan Antropologi Sastra dan Pembelajarannya di Sekolah Menengah Pertama (SMP) - Yuniarti, Endah; , Prof Dr. Ali Imron Al-Ma'ruf. M.Hum (2017)
The purpose of this study is (1) Describes the background sosiohistoris Afifah Afra as the novelist De Winst. (2) Describes the structure of the novel De Winst work Afifah Afra. (3) Presented aspects of Javanese culture in the novel De Winst work Afifah Afra. (4) Describes the results of the research literature, especially the novel in literature teaching junior level. Research using qualitative descriptive methods. Objects that are examined in this study is a sentence in the novel De Winst work Afifah Afra. The data source of this research is the novel De Winst work Afifah Afra. Data collection techniques, ie using library techniques, see, and record. Data analysis technique used is semiotic models, ie, heuristic and hermeneutic reading. The results of this study indicate that (1) the background sosiohistoris Afifah Afra was born on February 18, 1979 in Purbalingga. Afra was born in a simple family, but on the bigger picture. In addition, families Afra also attached to the feel of education, making small Afra grew into an active children who like to write and learn, ranging from history, anthropology, literature, to learn to cook. Afra decided to settle in the city of Solo after meeting with Ahmad Supriyanto and married in 2003. (2) The structure of the novel De Winst Afifah Afra works can be seen from the cohesion theme and the fact crita. Themes novel De Winst work Afra Afifah are shipwreck of a romance for indigenous Javanese palace. Flow used is a advanced or progresivve groove. The main character in this novel is Rangga. Background that is used in the Netherlands and Indonesia. (3) aspects of Javanese culture in the novel De Winst work Afra Afifah divided into (a) the religious system, covering the entire belief system, usually applied in limited groups. (b) kemayarakatan system, in this connection are restricted in the form of kinship and other social and political organizations that are considered relevant. (c) knowledge systems, encompassing various forms of human experience in relation to the nature of objectivity. (d) language, both oral and written. (e) kesnian, with various kinds, such as: art, sound art, the art of movement, and so on. (f) system of subsistence, is the central issue for the sustainability of human life. (g) equipment system of human life, this is to help facilitate in carrying out activities of human life. (4) novel De Winst Afra Afifah work can be implemented in learning Indonesian junior class IX semester of 2 (two).